Life cycle models for university-scale sounding rockets: A three-dimensional review - Salih Alsudairi, Ahmad Nayef; Mohd Rafie, Azmin Shakrine; Mohammad Algarni, Abdullah; Md Ali, Syaril Azrad; Gires, Ezanee; Abdullah, Amini Amir; Mohammad Aljuhaiman, Ibrahim (John Wiley and Sons Inc, 2024)
Designing a sounding rocket is an interdisciplinary activity, involving many domains and many stages. The alignment between the disciplines and life cycle stages is not straightforward. Much effort is required in life cycle model management and tailoring processes. In this article, an objective was set to make a comparative study and analysis of life cycle concepts related to Malaysian university-scale sounding rocket development, to assist in any future life cycle tailoring. Toward that goal, a comprehensive review and analysis of the related life cycle models was performed. The review covered three dimensions: engineering standards, aerospace vehicle design (AVD), and actual sounding rockets projects. Many reviewed models were re-prescribed using model-based systems engineering (MBSE) diagrams. This allowed greater insight and better assistance for any future tailoring. This expedition stresses the importance of the proposed three-dimensional reviewing of life cycles. Unconventional life cycle models (e.g., Western vs. Eastern) have also been included. It is argued that mapping the standards onto actual projects improved insight. One of the important outcomes is the demonstration of the importance of the concept of the centrality of the values in the development process, which shall govern the stakeholders’ requirements.